Digital Accessible Information System for the Sight-Disabled in the Netherlands and the Situation in Turkey - Ramazan Bakırcı (Türk Kütüphaneciliği)
This article is about the study visit made to Dedicon Productions, which provides library and training services for the sight-disabled in the Netherlands, to examine the application of the Digital Accessible Information System (DAISY). The article also briefly discussed the situation in Turkey.